Experimental investigation flexural behavior of reinforced concrete beam with partial replacement of vermiculite. (2021) - Naveenkumar, K.; Suriya, P.A.; Divahar, R.; Sangeetha, S.P.; Jayakumar, M.
Abstract: Reinforced concrete beam is a widely used composite material for structural element. The aim of the project is to study the flexural behavior of Reinforced concrete beam with replacement of vermiculite material. The percentage of replacement of vermiculite replacement for fine aggregate is decided based on the test results of compression and split tensile strength. The replacement is done in two proportions 5 %, 10 % for fine aggregate. From this compression strength test and split tensile strength test values. I conclude that 5 % of vermiculite is the optimum percentage that be replaced with fine aggregate. Then singly reinforced beam and doubly reinforced beam are casted with and without replacement of vermiculite and tested. The comparison of the conventional beam and 5% of vermiculite replaced beam has been done and concluded that it is possible to use reinforced concrete beam with 5% replacement of vermiculite. Experimental results indicate that the two-point loading on reinforced concrete beam with 5% replacement of vermiculite for fine aggregate gives high strength then the conventional reinforced concrete beam and self-weight of reinforced concrete beam can also be reduced considerably up to 10% then the conventional reinforced concrete beam.